Contribution of next generation sequencing in pediatric practice in Lebanon. A Study on 213 cases. Issue 6 (7th October 2018) - Nair, Pratibha; Sabbagh, Sandra; Mansour, Hicham; Fawaz, Ali; Hmaimess, Ghassan; Noun, Peter; Dagher, Rawane; Megarbane, Hala; Hana, Sayeeda; Alame, Saada; Lamaa, Maher; Hasbini, Dana; et al.
Abstract: Background: According to the Catalogue of Transmission Genetics in Arabs, less than half of diseases reported in Lebanese patients are mapped. In the recent years, Next Generation Sequencing (NGS) techniques have significantly improved clinical diagnosis, compared to traditional sequencing methods. Methods: A total of 213 analyses by NGS (167 by whole exome sequencing (WES) and 46 by multigene panels tests) were performed on pediatric patients across different regions of Lebanon over a period of two years (December 2015–December 2017). Results: Neurological disorders were the most frequent referral demand for both WES and gene panels (122/213). Pathogenic, likely pathogenic, or variants of unknown significance were identified in 69.5% of the WES and panel patients combined. Over half of the patients with such variants had an autosomal recessive disorder. A definite molecular diagnosis (pathogenic or likely pathogenic variants) was achieved in 34.1% and 47.8% of the patients studied by WES and the multigene panels, respectively. Thirty‐three novel variants were found in the cases that were molecularly solved; 26 of these being identified by WES and seven by the multigene panels. In three consanguineous families, autosomal recessive inheritance of genes previously reported as showing dominant inheritance patterns were found. Biallelism was found in six cases, digenism in four cases, and one case was trigenic. Conclusion: Our study thus suggests that NGS tools are valuable for an improved clinical diagnosis, and highlights that the increased adoption of such techniques will significantly further improve our understanding of the genetic basis of inherited diseases in Lebanon. Abstract : We present the results of a study which included a total of 213 analyses by NGS . Thirty‐three novel variants were found in the cases that were molecularly solved; and autosomal recessive inheritance of genes previously reported as showing dominant inheritance patterns were found.